The development of an in vitro model using equine hepatocytes and liver microsomes for the study of drug metabolism in the horse - Shibany, Khaled Ayad S. (2018)
Horses are extensively exposed to various kinds of medication. However, limited information is available about how these medications are metabolised in this species. Hence, the development of strategies and methods that provide a better understanding of different metabolic pathways for different drugs is of major importance. Although, the horse is considered as a monogastric animal, it is also a hind gut fermenting animal, i.e. most of the feed is degraded in the cecum and colon. Thus, it is hypothesised that this could result in an evolutionary difference in xenobiotic metabolising enzymes between human and horses which may lead to different pharmacokinetics. Therefore, the main aim of this study is to develop an in vitro model as a preclinical testing system of newly developed substances for horses using freshly isolated, cryopreserved equine hepatocytes and liver microsomes. Fresh hepatocytes were isolated and liver microsomes were prepared using livers which were obtained from horses, post slaughter. Part of the freshly isolated hepatocytes were cryopreserved. A comparison metabolic study was carried out to compare the three in vitro systems. The intrinsic clearance (Clint) of three drugs used in equine medicine omeprazole, flunixin and phenylbutazone, was determined via the substrate depletion method. The determined Clint values were extrapolated to in vivo hepatic clearance (ClH) using two in vitro liver models, namely, well stirred and parallel tube models. To perform the extrapolation step, the values of microsomal protein per gram of liver (MPPGL) and the number of hepatocytes per gram of liver in the horse (HPGL), also known as the hepatocellularity, key scaling factors in both the well-stirred and parallel tube models, were obtained for horse. These scaling factors were determined by comparing the CYP P450 content in microsomes and cryopreserved hepatocytes against the CYP P450 content of the liver. Additionally, HPGL was also calculated from the ratio of liver protein concentration to matched hepatocyte suspension protein concentration. Effects of ageing on CYP P450 content, MPPGL and HPGL values were also investigated. Furthermore, chloramphenicol’s potential effect on the in vivo AUC for omeprazole was predicted using microsomes. In the present study, freshly isolated equine hepatocytes were successfully cryopreserved and the viability of recovered cells, after a 30% Percoll gradient, was 77 ± 11% and estimated recovery rate was approximately 27%. MPPGL and HPGL values ranged 41-73 mg/gram of liver (mean= 57 mg/gram of liver, n=39) and 146 - 320 × 106 cells/g of liver (Average = 227× 106 cells/g of liver, n=18) using CYP P450 method; and 156 - 352 × 106 cells/g of liver (Average = 232× 106 cells/g of liver) using protein method. It was found that increase in age had no effect on CYP P450/mg microsomal protein content. This study successfully predicted the in vivo clearance for omeprazole, flunixin and phenylbutazone using, both, freshly isolated and cryopreserved equine hepatocytes. Meanwhile, microsomes significantly underpredicted the in vivo hepatic clearance ClH. However, microsomes were used in present study to perform drug-drug interaction (DDI) in vitro study between omeprazole and chloramphenicol. The average of IC50 and the inhibitor constant Ki of the three horses were 17.7±5.8 µM and 15.4±5 µM, respectively. The work presented in this thesis paves the way to develop in vitro models using equine hepatocytes and liver microsomes, which are reproducible, scalable and compatible with screening platforms. These models can be applied to the improvement of predicted detection times (DT) in horse racing which may aid veterinarians to estimate accurate withdrawal times; hence, the horse welfare will be improved. Moreover, further phase II metabolism, drug induction and comparative studies can be performed.